2013
DOI: 10.1371/journal.pone.0058262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dual Targeting of Tumor Cells and Stroma in Human Glioblastoma Xenografts with a Tyrosine Kinase Inhibitor against c-MET and VEGFR2

Abstract: Anti-angiogenic treatment of glioblastoma with Vascular Endothelial Growth Factor (VEGF)- or VEGF Receptor 2 (VEGFR2) inhibitors normalizes tumor vessels, resulting in a profound radiologic response and improved quality of life. This approach however does not halt tumor progression by diffuse infiltration, as this phenotype is less angiogenesis dependent. Combined inhibition of angiogenesis and diffuse infiltrative growth would therefore be a more effective treatment approach in these tumors. The HGF/c-MET axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 36 publications
5
77
1
Order By: Relevance
“…These results confirm a key role of c-Met in GBM progression. 29,[48][49][50][51] The lack of regulation of PY142 b-catenin by a c-Met inhibitor does not allow us to conclude if c-Met is phosphorylating this b-catenin site in GBM cells and rather suggests the involvement of other kinases. The proteolytic processing of c-Met is well described and nuclear c-Met has been linked to invasive cancers.…”
Section: Resultsmentioning
confidence: 96%
“…These results confirm a key role of c-Met in GBM progression. 29,[48][49][50][51] The lack of regulation of PY142 b-catenin by a c-Met inhibitor does not allow us to conclude if c-Met is phosphorylating this b-catenin site in GBM cells and rather suggests the involvement of other kinases. The proteolytic processing of c-Met is well described and nuclear c-Met has been linked to invasive cancers.…”
Section: Resultsmentioning
confidence: 96%
“…[39,40] Inhibitors of c-MET such as cabozantinib are also being considered, and have been reported to induce a significant increase in overall survival of mice bearing GBM xenografts. [41] However, anti-angiogenic therapies targeting VEGF/ VEGFR have had less of an effect than expected. [42] This could be because, in highly vascularized tissues like the lung and brain, tumors can often proliferate around existing vessels and hijack them, a process called vessel cooption.…”
Section: Angiogenesismentioning
confidence: 99%
“…As a multitargeted kinase inhibitor, cabozantinib can act through blocking several RTKs, including KIT, but also other kinases some authors postulate a potential role in GIST as shown in several preclinical models and patient samples (20,32,33). One of cabozantinib's targets is MET, the tyrosine kinase receptor for hepatocyte growth factor which is implicated in the resistance to different TKIs or monoclonal antibodies in several preclinical models and human tumors (34)(35)(36).…”
Section: %mentioning
confidence: 99%